Impact of Water Scarcity on Domestic Water Use in Drought-prone Barind Tract, Bangladesh: A Sociological Perspective - Jahura, Sultana; Islam, M. Zulfiquar Ali; Mostafa, M.G (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
The Barind tract (northwest part of Bangladesh) is facing the prevailing disaster of drought due to extreme climatic conditions, including low rainfall. This research attempts to measure the character of the domestic water crisis and the adaptation capacity of the drought-affected Barind people. It also investigates the impact of climate-induced water scarcity on the socioeconomic livelihood of respondents in two villages of the Tanore sub-district in Rajshahi district, which is the most drought-prone area in the Barind tract. In the study area, face-to-face interviews (n = 246) through a structured questionnaire with the respondents of two villages were conducted in an affable environment to collect primary (quantitative) data. In-depth interviews were also conducted with two farmers to collect qualitative data for the study. So it is mixed-method research. All the gathered data were examined using Atlas TI, SPSS, and GIS software. The results of this research show an extended scenario of excessive use of groundwater for domestic purposes due to water table depletion. It presents a portfolio of the sufferings of domestic water users in the study area, not only during the load-shedding period but also during the lack of technical support. Few people are bound to use more contaminated pond water for applying artificial fish feed. Poor inhabitants who depend on others for domestic water are facing more critical conditions due to the inability to install deep-tube wells at a higher cost. As a result, people need to move further away to collect fresh groundwater for domestic use.